Overdose Receiving Centers – An Idea Whose Time Has Come?. (2nd January 2022) - Hern, H. Gene; Goldstein, David; Tzvieli, Ori; Mercer, Mary; Sporer, Karl; Herring, Andrew A.
Abstract: Drug overdose deaths have been the leading cause of accidental death in the United States with two thirds involving opioids. Strong evidence supports the efficacy of medications for addiction treatment such as buprenorphine and harm reduction strategies such as naloxone distribution. While emergency medical service (EMS) systems have defined specialty centers for the treatment of many significant life threatening disease (trauma, stroke, myocardial infarction) implementation of opioid use disorder systems of care that integrate EMS are uncommon. As fentanyl drives the third wave of the opioid epidemic, EMS systems are uniquely positioned to direct patients to hospitals that can provide the best care for patients with Opiate Use Disorder (OUD.) Emergency Departments which have established systems for early intervention and treatment for patients with opioid use disorders have shown higher engagement in treatment programs. This, in turn, leads to lower mortality. EMS systems which designate specialty centers for overdose patients may show a public health mortality benefit.